MESIN PEMUSNAH SAMPAH MULTIGUNA UNTUK LINGKUNGAN PEDESAAN - Setyawan, Azis Budi; Koswara, Engkos; Warandi, Rofandi Rori Aditiar (Universitas Majalengka, 2025)
Waste is the main cause of environmental pollution in Indonesia, with 36.11 million tons of waste generated annually according to the Ministry of Environment and Forestry (KLHK) in 2022. Only 63.53% of this waste is managed, while the rest remains poorly handled. In Cibogo District, Sadawarna Village produces 0.5 tons of plastic waste per day, with waste management still suboptimal and public awareness relatively low. This issue leads to environmental pollution and poses a threat to public health. As a solution, the use of a Waste Disposal Machine is expected to improve waste management in Subang District. The methods carried out include data collection through journals, observation, and interviews at the Center for Appropriate Technology Research (PRTTG) BRIN, followed by blueprint analysis, work preparation, manufacturing processes, manufacturing assembly, performance testing, and finishing. The manufacturing process of the thermal waste disposal machine is divided into several components, with operations including measurement, cutting, rolling, threading, bending, drilling, and welding. Based on the continuous performance test results, when 20 kg of waste was inserted into the combustion chamber for 10 minutes, the prepared waste was immediately placed into the combustion chamber for further incineration until all available waste was fully processed. The temperatures obtained during the waste incineration process were 287ºC in the lower chamber, 778ºC in the middle chamber, and 62ºC inside the oven. The emissions produced during waste incineration showed the following changes: HCHO from 0.042 to 0.047, PM₂.₅ from 26 to 304, TVOC from 0.286 to 0.004, CO from 4 to 2, CO₂ from 487 to 399, temperature from 26ºC to 29ºC, RH from 67% to 59%, and AQI from 18 to 86. Based on these data, the emissions released by the waste disposal machine remain within normal limits and are not considered hazardous.